2022
DOI: 10.3390/jcm11113104
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D for Clinical Diseases in Women: An Indispensable Factor in Medicine and Dentistry

Abstract: Vitamin D, commonly known as the “sunshine vitamin”, is a secosteroid hormone. It is recognized for its neuroprotective role in brain development and it has a key role in bone metabolism, muscle function, oral health, and temporomandibular disorders. Vitamin D is involved in a range of important physiological processes, such as promoting cell growth and differentiation, facilitating immunomodulation regulation, neurotransmission, and alleviating anti-inflammatory effects. Vitamin D deficiency is known to be im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Therefore, vitamin D might have a key role in a comprehensive rehabilitation approach to COPD-related disability targeting physical performance and pulmonary function [ 94 , 95 , 96 ]. In addition, to the best of our knowledge, vitamin D and calcium supplementation has been associated with any pharmacological drug prescribed in COPD patients with osteoporosis and should be considered a milestone of the general therapeutic approach to osteoporosis [ 97 , 98 , 99 , 100 , 101 , 102 , 103 ].…”
Section: Nutraceuticals and Dietary Supplementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, vitamin D might have a key role in a comprehensive rehabilitation approach to COPD-related disability targeting physical performance and pulmonary function [ 94 , 95 , 96 ]. In addition, to the best of our knowledge, vitamin D and calcium supplementation has been associated with any pharmacological drug prescribed in COPD patients with osteoporosis and should be considered a milestone of the general therapeutic approach to osteoporosis [ 97 , 98 , 99 , 100 , 101 , 102 , 103 ].…”
Section: Nutraceuticals and Dietary Supplementsmentioning
confidence: 99%
“…Denosumab, a fully human IgG2 monoclonal antibody against Receptor Activator of Nuclear factor Kappa B (RANKL-B), has been proposed to treat osteoporosis patients by reducing the rate of clinical fragility fractures (both hip and vertebrae) [ 97 ]. Denosumab is administrated as a subcutaneous injection of 60 mg once every 6 months.…”
Section: Pharmacological Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, our regression machine learning model analysis highlighted that vitamin D serum levels have been associated with higher weight of influence on the DMFT score. In the last few decades, the nutritional consequences of vitamin D deficiency on periodontal health represented a matter of interest [ 20 , 53 , 54 , 55 ]. By a recent systematic review with meta-analysis, Machado et al [ 53 ] reported that patients with chronic periodontitis had lower serum levels of vitamin D than periodontally healthy patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, bisphosphonate-related osteonecrosis of the jaws [ 16 ], oral lesions [ 15 ], caries [ 17 ], and periodontal tissue diseases (e.g., gingivitis and periodontitis) [ 18 , 19 ] may occur in a higher percentage of BC women undergoing cancer treatments and anti-osteoporotic drugs. Similarly, vitamin D plays a key role in different fields of medicine, including dentistry, and acts through several mechanisms, including cellular proliferation and differentiation, cell maturation, and innate immune system response [ 20 ]. Moreover, high serum vitamin D3 levels may be strongly associated with an increase in the overall survival rate of BC patients [ 21 , 22 ], and this could be related to the fact that both vitamin D3 and vitamin D receptors (VDR) are involved in BC pathogenesis.…”
Section: Introductionmentioning
confidence: 99%